Harassment of Filipino journalists In the Ramos administration A continuing saga from the Marcos and the Aquino eras - Agapito, Benigno Belda Jr.; Domingo Jr., Ben G. (Quezon City College of Mass Communication, University of the Philippines Diliman, 1993)
"The investigative report is a three-part story on the continuing media harassment in the Philippines. The report tackles specific cases of harassment in the Ramos administration which is described as an exact replica of the Marcos and the Aquino eras with respect to media harassment and curtailment of press freedom. The first part, Target: Critical Filipino Journalists, reveals some cases of harassment in the Ramos administration and focuses on the mysterious disappearance of Voice of Zambales publisher-columnist Romeo Legaspi. The second part, Justice Delayed, Justice Denied, discloses the unending investigations and the failure to prosecute even just one of the culprits in media harassment cases especially under the Ramos government. The last part, Ramos' Year of Journalism' edict an 'Irony', bares how the Ramos' proclamation of August 30, 1992 to August 30, 1993 as "The Year of Journalism in the Service of the Nation" was mere rhetorics which all the more dissatisfies Filipino journalists."
Vita.
Thesis (A.B. Journalism)--University of the Philippines Diliman